The Role Of Community Intervention In Creative Economy Industry Players In Improving Social Welfare : Study on the "Jarpuk Rindang" Community, Central Lombok Regency, West Nusa Tenggara Province - Yurita Puji Agustiani; Isbandi Rukminto Adi; Triyanti Anugrahini (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study is to determine the current conditions experienced by weaving craftsmen in Central Lombok, especially in the "Jarpuk Rindang" community. The research that will be carried out is an empowerment intervention for the community. This community consists of women who produce weaving with Lombok motifs. Weaving produced by this community has been introduced and sold throughout Indonesia and even abroad. The problem to be discussed in this research is that this community has received intervention from the government as well as the private sector for product development, but the results have not been maximized in the market. Competition with products produced using technology such as print or online sales competition is still not optimal. This research looks at the current condition of the welfare of the craftsmen and what interventions have been carried out in this community and how the quality of the products that have been produced. This research will also be deepened by looking at what other potentials this community has and whether this potential can be utilized optimally. This research will be conducted using a qualitative method where this research will involve community administrators and 50 craftsmen as data representatives from the community with criteria that include age, status, and experience as weavers by collecting data which is carried out through surveys and observations. Data collection techniques used are Questionnaire, in-depth interviews, direct observation. The tools used in this research are face to face and data analysis techniques with narrative analysis. The results of the analysis found that this community lacked proper empowerment intervention programs according to the needs of the weavers so that product quality was still not optimal and marketing assistance was needed to maximize it. The ability of the craftsmen in this community has great potential if managed properly so that it will have a real impact on the income of the weavers and will improve the welfare of the weavers. Based on the results of the analysis, it can be concluded that a prior approach is needed in carrying out community interventions to dig deeper into what interventions are needed for the community, besides that it is also necessary to analyze the possibilities of the skills and potential of the community that can be developed to promote members in the community as possible in the form of collaboration, innovation, and the addition of skills that support this potential. In an empowering role, people with social entrepreneurship who are truly able to analyze the needs of weavers and pay attention to the impact on their welfare are needed.